Willingness to pay for biofertilizers among grain legume farmers in northern Ghana - Banka, M.; Aidoo, R.; Abaidoo, Robert C.; Fialor, S.C.; Masso, C. (Sciencedomain International, 2018)
Background: The call for use of improved Soil Fertility Management (SFM) technologies is a prerequisite to increase agricultural productivity among farmers. This study assessed farmers’ willingness to pay (WTP) for selected financially rewarding biofertilizer technologies/packages for legume production in northern Ghana. Primary data was elicited from 400 grain legume farmers selected from Northern and Upper West Regions of Ghana through a simple random sampling technique. The double bounded dichotomous choice (DBDC) format of contingent valuation approach was employed to elicit willingness to pay values and determinants of farmers WTP was evaluated using the maximum likelihood estimation procedure. Results: The results showed that about 60%, 25% and 46% of soya, cowpea and groundnuts farmers were willing to pay for the selected biofertilizers (Biofix, BR3267 and Legumefix respectively) at prices not exceeding GHC 14.00, GHC 28.00 and GHC 20.00 per 0.2kg of the respective biofertilizers. Legume farmers in Northern Region were however willing to pay higher for the three biofertilizer technologies as compared to their counterparts in Upper West Region. For 0.2 kg each of Biofix, BR3267 and Legumefix, farmers in Northern Region were willing to pay approximately GHC 17.00, GHC 12.00 and GHC 23.00 respectively whereas those in Upper West Region were willing to pay GHC 14.00, GHC 9.00 and GHC 11.00 for the same quantity of each biofertilizer. The study identified farming experience, FBO membership, awareness and previous use of biofertilizers as significant determinants of farmers’ willingness to pay for Biofertilizers. Conclusion: Comparatively, mean prices farmers are willing to pay for these three technologies are below ex-factory prices, hence subsidizing the cost of production of these biofertilizers in the initial stages would be relevant for improving farmers’ uptake of these fertilizers. Sustained awareness creation through periodic education and sensitization by using FBOs as leverage points is also highly recommended to improve farmers’ understanding of the concept of biofertilizer use.